A RESEARCH PROGRAM. - Wildman, J. R. (The Accounting Review, 1926)
Abstract The article presents information related to a research program conducted in business firms. The idea behind the working out a scheme of technical procedure a little more comprehensive and sound than, perhaps, it had been in the past. The first subject on which being investigated was cash. The researchers were led to that by reason of the fact that fraud had been rampant as is known during the past two or three years. Cash irregularities have increased tremendously in number and amount and volume and perhaps cash of all the assets is the most easily manipulated and stolen. In working out the program in connection with cash, three men of considerable experience in the profession met and formulated, out of their own experience, a program directed at the verification of cash balances and the accuracy of the cash records, all with a view of detecting any and all forms of cash irregularities–rather a pretentious undertaking, of course. After setting up this ideal or theoretical procedure they compiled from reports about 75 or 80 cases representing actual cash irregularities, giving consideration to the manner in which it bad been concealed and the method employed in the detection of the irregularity. Having set up the ideal procedure out of experience, they then proceeded to test these cases against that procedure, finding, of course, a number of weak spots, which then was corrected and strengthened, finally utilising the resulting procedure as a basis for the work of the organization in the verification of cash.